1984
DOI: 10.1159/000115676
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Clinical Aspects of Parkinson Patients with Intellectual Impairment

Abstract: The present study is based on the hypothesis that Parkinson’s disease is not a single homogeneous entity and that parkinsonians with intellectual impairment are a distinct subgroup of the parkinsonian population. An assessment of cognitive functions was performed on 70 patients with Parkinson’s disease and on 90 control patients. Analysis of their performances led to the division of parkinsonians into two subgroups: with and without neuropsychological impairment. Investigation of the clinical characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…At the second assessment, 7 parkinsonians had devel oped deterioration of cognitive functions, according to our criteria [24], Whereas their intellectual capacity was good at time of the first assessment, all 7 parkinsonians showed a loss of intellectual abilities sufficiently severe to impair so cial or occupational functions, according to DSM-III cri teria [38], With respect to the degree of mental deterio ration, some information may be provided by the type and number of tests showing a decline in performance. Two parkinsonians showed a deterioration in five tests of mental status evaluation, 2 in four tests and 3 in three tests (table III).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…At the second assessment, 7 parkinsonians had devel oped deterioration of cognitive functions, according to our criteria [24], Whereas their intellectual capacity was good at time of the first assessment, all 7 parkinsonians showed a loss of intellectual abilities sufficiently severe to impair so cial or occupational functions, according to DSM-III cri teria [38], With respect to the degree of mental deterio ration, some information may be provided by the type and number of tests showing a decline in performance. Two parkinsonians showed a deterioration in five tests of mental status evaluation, 2 in four tests and 3 in three tests (table III).…”
Section: Resultsmentioning
confidence: 95%
“…The patients were selected at the Parkinson's Disease Center of the Department of Neurology in Perugia (Italy) and were periodi cally examined with a standard physical, neurological, neuropsycho logical and psychiatric assessment [24], They all met the following criteria: 50-65 years of age, disability score of 3 on the Hoehn-Yahr scale [25], ischemia score of less than 4 [26], absence of depression on psychiatric interview, normal CT brain scan, and no evidence of cognitive impairment by neuropsychological examination (see Pro cedure). This selection resulted in a total of 30 patients, 21 males and 9 females.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study, however, a marked increase of SPLI in CSF was described, sug gesting that a compensatory increase in SP-ergic neu ronal activity might occur when dopaminergic transmis sion is failing [21], We studied CSF SPLI and SLI in a small group of senile patients with parkinsonism and report our findings because of the clinical interest of evaluating the CSF neuropeptide status and the possible pathophysiological significance of changes. Late onset PD appears to have pathological relationships with SDAT [5,7,22] and for comparative purposes we include results of CSF SPLI and SLI measurements in patients with SDAT, published in detail elsewhere [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [11], we suggested that there exists a subgroup of parkinsonian patients in whom dementia is a prominent picture. Parkinsonians with impaired mental functions were found to differ from other parkinsonians in several respects, including more marked severity of the extrapyramidal syndrome (with predominant bradykinesia) and an early loss of response to levodopa treatment.…”
Section: Discussionmentioning
confidence: 88%